2011
DOI: 10.3409/fb59_3-4.151-155
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Induces Endogenous Hydrogen Sulfide Tissue Concentration Changes in Various Mouse Organs

Abstract: Carvedilol induces endogenous hydrogen sulfide tissue concentration changes in various mouse organs. Folia biologica (Kraków) 59: 151-155. Carvedilol, a third generation non-selective adrenoreceptor blocker, is widely used in cardiology. Its action has been proven to reach beyond adrenergic antagonism and involves multiple biological mechanisms. The interaction between carvedilol and endogenous gasotransmitter hydrogen sulfide (H S) is unknown. The aim of the study is to assess the influence of carvedilol on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…Рівень H 2 S в міокарді визначали за методикою [11]. Міокард промивали холодним 1,15 % розчином KCl, подрібнювали ножицями, гомогенізували в серед-овищі 0,01 М NaOH у співвідношенні 1:5 (маса/об'єм) при 3000 об/хв (тефлон-скло).…”
Section: матеріали та методи дослідженняunclassified
“…Рівень H 2 S в міокарді визначали за методикою [11]. Міокард промивали холодним 1,15 % розчином KCl, подрібнювали ножицями, гомогенізували в серед-овищі 0,01 М NaOH у співвідношенні 1:5 (маса/об'єм) при 3000 об/хв (тефлон-скло).…”
Section: матеріали та методи дослідженняunclassified
“…Вміст модуляторів печінкового стеато-та фіброгене-зу -гомоцистеїну, туморнекротичного фактору аль-фа (ТNF-α) та IGF-1 в сироватці крові визначали іму-ноферментним методом за наборами «Homocysteine EIA»; «Rat TNF-α ELISA Kit»; «m/r IGF-1-ELISA (IGFBP-blocked)»; відповідно до інструкції фірми-ви-робника на аналізаторі STAT FAX 303/PLUS. Вміст H 2 S в печінці визначали як описано у дослідженні [21]. Печінку перфузували холодним 1,15 % розчином KCl, наважку тканини гомогенізу-вали протягом 1-2 хв.…”
Section: матеріали і методи дослідженняunclassified
“…While increased generation of hydrogen sulphide (H 2 S) by garlic and metformin may enhance mitochondrial function and rescue eNOS from peroxynitrite-induced uncoupling (Benavides et al, 2013;Wilinski et al, 2013;Guo et al, 2012;Gu et al, 2012). Garlic and metformin may help prevent AD and depression partly through H 2 S which upregulates nitric oxide production (Wilinski et al, 2011). Studies (Kamat et al, 2015; have shown that hydrogen sulphide attenuates homocysteine-induced mitochondrial toxicity and neurodegeneration mediated through NMDA receptors, implicating a possible preventive action of metformin and garlic.…”
Section: Garlic May Potentiate the Effects Of Metforminmentioning
confidence: 99%